Macroeconomic trade effects of vehicle currencies: Evidence from 19th century China - Makram El-Shagi; Lin Zhang (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2016)
We use the Chinese experience between 1867 and 1910 to illustrate how the volatility of vehicle currencies affects trade. Today's widespread vehicle currency is the dollar. However, the macroeconomic effects of this use of the dollar have rarely been addressed. This is partly due to identification problems caused by its international importance. China had adopted a system, where silver was used almost exclusively for trade, similar to a vehicle currency. While being important for China, the global role of silver was marginal, alleviating said identification problems. We develop a bias corrected structural VAR showing that silver price fluctuations significantly affected trade.
urn:nbn:de:gbv:3:2-59308
Keywords: C32; F14; F31; F41; N15; 330; vehicle currency; China; SVAR; small sample